Front Cover: Rapid automatic creation of monodisperse emulsion droplets by microfluidic device with degassed PDMS slab as a detachable suction actuator. Issue 3 (2nd February 2018) - Murata, Yuki; Nakashoji, Yuta; Kondo, Masaki; Tanaka, Yugo; Hashimoto, Masahiko
Abstract : DOI:10.1002/elps.201700247 The cover picture shows rapid automatic creation of monodisperse emulsion droplets achieved in a new microfluidic device. The device features five layers, including a degassed polydimethylsiloxane slab as a detachable liquid‐suction actuator. The actuator is stacked on a lower microfluidic layer. The micropillars on the surfaces of the polydimethylsiloxane slab provide a large surface area for air dissolution. This air dissolution increases the vacuum level inside the closed outlet space within the device, leading to rapid liquid flow and a high droplet generation rate of ca. 470 droplets per second.